Evaluation of the Ocular Surface Parameters in Pseudoexfoliation Syndrome and Conjunctivochalasis - Sibel Kocabeyoğlu; Murat İrkeç; Mehmet Orhan; Mehmet Cem Mocan (Türk Oftalmoloji Dergisi, 2012)
Pur po se: To evaluate the ocular surface parameters in pseudoexfoliative (PEX) patients with conjunctivochalasis (CCh). Ma te ri al and Met hod: Fifty-three eyes of 53 patients with PEX syndrome and 107 eyes of 107 subjects without PEX were enrolled in this study. All subjects were categorized into two groups according to the presence or absence of CCh. The ocular surface characteristics were evaluated with standard tear break-up time testing (BUT), lissamine green (LG) staining of the conjunctiva and cornea, and Schirmer I test with topical anesthesia. Patients were also assessed with the Ocular Surface Disease Index (OSDI) questionnaire with respect to the severity of their subjective symptoms. The Mann-Whitney U-test, student’s t-test, and logistic regression analysis were used for statistical evaluations. Re sults: Among the 160 subjects, 30 (56.6%) in the PEX group and 38 (35.5%) in the control group had CCh (p=0.018). Logistic regression adjusted to gender and age showed that eyes with PEX were 2.3 times (odds ratio, 95% CI: 1.1 to 4.6) more likely to develop CCh than eyes without PEX (p=0.015). There were significant differences in the BUT scores, Schirmer values, LG staining scores and the OSDI scores of patients who had PEX and those without PEX. Dis cus si on: The frequency of CCh is significantly higher in patients with PEX syndrome. Both PEX and CCh affect the ocular surface test results. It seems reasonable to evaluate and follow up PEX patients for CCh and ocular surface disease.. (Turk J Ophthalmol 2012; 42: 332-5)